2017
DOI: 10.1111/cen.13367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative anti‐thyroglobulin antibody in differentiated thyroid cancer

Abstract: Positive preoperative serum TgAb is associated with worse primary tumour characteristics but rarely showed poor prognosis, probably due to more aggressive treatment of these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(77 reference statements)
5
14
1
Order By: Relevance
“…This may indicate that autoimmunity is more powerfully manifested when both serum markers and target organ damage are present. Our finding that preoperative TgAb positivity had no significant influence in this regard is consistent with previous finding which may further indicate that the TPOAb status is more closely related to CLT than TgAb.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may indicate that autoimmunity is more powerfully manifested when both serum markers and target organ damage are present. Our finding that preoperative TgAb positivity had no significant influence in this regard is consistent with previous finding which may further indicate that the TPOAb status is more closely related to CLT than TgAb.…”
Section: Discussionsupporting
confidence: 92%
“…Jo et al . previously compared the disease persistence/recurrence in accordance with the preoperative TgAb status in patients with DTC but found no significant differences . Despite the fact that TPOAb and TgAb have similar immunologic properties, TPOAb is considered to be superior in predicting thyroid autoimmunity and detecting CLT than TgAb .…”
Section: Introductionmentioning
confidence: 99%
“…Some reports showed less extrathyroidal invasion [12,22,29,[48][49][50], but others more [7,19,51] in PTCs with thyroid autoimmunity. Similarly, some showed less lymph node metastasis [12,29,36,48,51,52], but others more [16,18,28,53,54].…”
Section: Is Thyroid Autoimmunity Beneficial For or Harmful Against Thmentioning
confidence: 98%
“…Regarding distant metastasis, Shen et al reported more cervical lymph node metastasis but less distant metastasis in anti-Tg-antibody positive group [53], suggesting that the positive anti-Tg antibody status could be a risk factor for metastatic cervical lymph nodes but a protective factor for distant metastasis. Jo et al also concluded that positive anti-Tg antibodies, even without anti-TPO antibodies nor lymphocyte infiltration, are associated with worse primary tumor characteristics (higher rates of lymphatic invasion and lymph node metastasis) but rarely show poor prognosis [54]. They speculated that this might be attributed to more aggressive treatment of these patients.…”
Section: Is Thyroid Autoimmunity Beneficial For or Harmful Against Thmentioning
confidence: 99%
“…Vasileiadis et al [ 20 ] reported that DTC patients with TgAb showed more frequent lymph node metastasis than those without TgAb (20.3% vs. 10.0%). Another study also found that elevated preoperative serum TgAb levels in DTC patients were significantly associated with adverse primary tumor characteristics, including nonencapsulated tumors, lymphatic invasion, and lymph node metastasis [ 34 ]. Similarly, Zhang et al [ 35 ] found that DTC patients with TgAb had a significantly higher rate of metastasis of cervical lymph nodes, and that lymph node stage was the only independent indicator for persistent TgAb (OR, 3.183).…”
Section: Preoperative Tgab Levels In Predicting the Prognosis Of Thyrmentioning
confidence: 99%